(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Anthropometry and physiology assume an essential part in choosing the specific form of the body with different estimations of the portions of the body it has additionally its significance in the recorded of Football and Kho-Kho amusement.